Comparable outcomes for pediatric acute lymphoblastic leukemia patients receiving conditioning with total body irradiation or chemotherapy: A nationwide, Korean registry‐based study - Kyung Taek Hong; Jung Yoon Choi; Hyery Kim; Ho Joon Im; Seung Min Hahn; Chuhl Joo Lyu; Hee Young Ju; Keon Hee Yoo; Eu Jeen Yang; Sung‐Soo Yoon; Hyeon Jin Park; Hyoung Soo Choi; et al. (HemaSphere, 2025)
Abstract Acute lymphoblastic leukemia (ALL) is the predominant malignancy in pediatric patients, and allogeneic hematopoietic stem cell transplantation (HSCT) plays a critical role in high‐risk cases. However, real‐world nationwide data comparing the outcomes of conditioning regimens are limited. This nationwide registry‐based study analyzed data from 270 Korean pediatric patients with high‐risk or relapsed ALL who underwent their first allogeneic HSCT with myeloablative conditioning. Among all analyzed patients, 118 received total body irradiation‐based conditioning (MAC‐TBI) and 152 received chemotherapy‐based conditioning (MAC‐Chemotherapy), of whom 96.6% underwent busulfan‐based regimens. MAC‐TBI recipients were older at diagnosis and at HSCT. No significant differences were observed between groups in neutrophil or platelet engraftment times, or infused CD34+ cell doses. Acute graft‐versus‐host disease (GVHD) incidences (grades II–IV and III–IV) were comparable, although chronic GVHD incidence tended to be lower in the MAC‐Chemotherapy group (21.0% vs. 31.1%, P = 0.072). Additionally, the 5‐year event‐free survival (EFS) rates for MAC‐TBI versus MAC‐Chemotherapy were 73.7% and 69.8% (P = 0.827), respectively; the 5‐year overall survival (OS) rates were 76.3% and 80.2% (P = 0.941), respectively, indicating that conditioning regimen did not significantly impact survival. Pediatric disease risk index, recent HSCT era, haploidentical donor type, and pre‐transplant disease status independently influenced EFS and OS, whereas anti‐thymocyte globulin administration significantly improved moderate‐to‐severe chronic GVHD, leukemia‐free survival. This nationwide real‐world analysis demonstrated comparable outcomes between myeloablative TBI‐based and chemotherapy‐based conditioning regimens in pediatric patients with ALL. These findings may inform the development of improved treatment strategies for this patient population.